Boundless settlements – tendencies and future of urban sprawl in the agglomeration of Budapest - Illyés, Zsuzsanna; Pádárné Török, Éva; Nádasy, László; Földi, Zsófia; Vaszócsik, Vilja; Kató, Eszter (Acta Geographica Debrecina Landscape & Environment series, 2016)
The Budapest agglomeration is a rapidly changing environment. Urban sprawl has been a prominent process in municipalities around the Hungarian capital, and its pace has significantly increased since the change of regimes. In our paper, we analyse the tendencies of urban development, the role of territorial protection and the types of land use mostly threatened by urban sprawl in two study areas within the Budapest agglomeration. A significant part of the Northern study area – located on Szentendre Island – is under territorial protection, while the Southern study area – located on Csepel Island – has a considerably lower amount of protected areas. We found that the settlements of the Northern study area have been expanding at a much slower pace than their Southern counterparts, where in the absence of effective restrictions, extensive areas – mostly former agricultural fields – have been converted into built-up areas. In addition, the Spatial Plan of the agglomeration allows the same tendencies to continue in both areas in the future as well.